Hvalfangsten i Antarktis 1956-57; en orientering (Polarboken, 1957)
Keywords: Sørishavet; hvalfangst

Kartlegging i Dronning Maud Land - Bergersen, Alf (Polarboken, 1957)
Keywords: Dronning Maud Land; kartlegging

De første i Antarktis - [Borchgrevink, Carsten Egeberg] (Vi Menn, 1957)
Keywords: Antarktis; Southern Cross; biografier; ekspedisjonen; oppdagelsesreiser

Gjenfunne hvalmerker i Antarktis i sesongen 1956/57 = Whale marks recovered during the Antarctic whaling season 1956/57 - Brown, S G (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Norway and the Antarctic - Evensen, Jens (The American Scandinavian review, 1957)
Keywords: Antarktis; historie; internasjonal politikk; norske ekspedisjoner

Til Dronning Maud Land med den norske Antarktis-ekspedisjon - Helle, Sigurd G (Polarboken, 1957)
Keywords: Dronning Maud Land; ekspedisjoner; logistikk

Er det ønskelig og forsvarlig å utvide sesongen for fangst av knøl i Sydishavet? = Is it desirable and justified to extend the open season for humpback whaling in the Antarctic? - Jonsgård, Åge; Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; marinbiologi

Upper winds over an Antarctic Station - Robin, Gordon de Quetteville (Quarterly Journal of the Royal Meteorological Society, 1957)
Preliminary results from the Norwegian-British-Swedish Antarctic expedition 1949-52. A preliminary note on the upper-air temperatures over Maudheim, the base of the Norwegian-British-Swedish Antarctic Expedition 1949-1952, has already been published by Nils Jorgen Schumacher (1955). This note is intended to throw further light on some points raised in Schumacher's paper and to outline the general pattern of upper winds over Maudheim. Owing to the use of a radio theodolite, the data gave a representative picture of the wind structure over an Antarctic station without the excessive bias of previous observations which were limited to periods of clear weather. The detailed report and discussion of aerological observations made at Maudheim will be published shortly by the Norwegian Polar Institute.
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; meteorologi

Norsk kartleggingsarbeid i Antarktis: kaptein H.E. Hansen fyller 70 år = Norwegian mapping in the Antarctic: captain H.E. Hansen reaches his 70th birthday - Ruud, Johan T (Norsk hvalfangst-tidende, 1957)
Keywords: Antarktis; Sørishavet; biografi; historie; kartlegging

Rapport om hvalmerking utført av norske hvalbåter i Antarktis i sesongen 1955/56 = Report on whale marking carried out by Norwegian catchers in the Antarctic season 1955/56 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

En underbeskattet knølhvalbestand? = An underfished humpback population? - Symons, H W; Weston, R D (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marinbiologi